BALANITES AEGYPTIACA PROTECTION AGAINST PROLIFERATION OF DIFFERENT CANCER CELL LINE - Al-Malki, Abdulrahman L.; Barbour, Elie K.; Abulnaja, Kalid O.; Moselhy, Said S.; Kumosani, Taha A.; Choudhry, Hani (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of the present study was to evaluate in vivo anti-tumor activity of Balanites aegyptiaca fruits extracts in addition to its role in cell cycle and apoptosis. Materials and Methods: Antitumor activities of ethylacetae extract (EAE), ethanol extract (EE) and chloroform extract (CE) were tested against different cell line Hep-2, MCF-7, HL-60 and HCV29T. Calculation of the IC50 values for these extracts confirmed that the most potent plant extract was EAE (40 ug/ml) followed by EE (55ug/ml), CE (61ug/ml). Results: The ethanolic and chloroform extracts showed lower difference in their potency, while the EAE was found to be more active indicating for nonpolar active principles responsible for the anti-proliferative activity. The ethanolic extract was three times higher active than the chloroform extract. The results obtained showed that EAE exert a significant anti-proliferative, enhancement of apoptosis and modulation of cell cycle phases compared with vincristine. Conclusion: The presence of alkaloids, flavonoids and Phenolics increase its efficiency as anti-proliferative action. EAE has promising anti-cancer activity with higher activity than EE or CE extracts